Collaboration between schools and museums for inclusive cultural education: Findings from the INARTdis-project - Gigerl, Monika; Sanahuja-Gavaldà, Josep M.; Petrinska-Labudovikj, Rozita; Moron-Velasco, Mar; Rojas-Pernia, Susana; Tragatschnig, Ulrich (Frontiers in Education, 2022)
The increasing heterogeneity in our communities is a reality and a foundational element of modern societies. This article deals with different aspects of political, social and cultural participation, processes of integration and inclusion. The aim of inclusion of all marginalized groups, among others integrating migrant communities, has to be a process of involving all sides—the local communities with publicly funded cultural institutions, the marginalized groups like migrant communities and the educational institutions in the local area. Therefore, the local community and schools have to be willing to make efforts in addressing interests and needs of all people, especially migrants or persons with disabilities. This paper presents the findings of the data collection in the project INARTdis in the countries Austria, Spain, North Macedonia and Portugal. Firstly, educators from the school and extracurricular sector as well as people from the fields of culture were asked to answer the question: What is inclusive arts education and how can this be promoted through cooperation? The analysis of inclusive access to cultural institutions and arts education was conducted in 2021 using a mixed-method design. Secondly, during museum visits, results on the learners’ perspectives were collected. The aim was to find out what makes it easier for visitors to access the museum? The results show that, although the institutions and their professionals assume the principles of inclusion, their implementation is complex, either due to a lack of resources or due to the organizational structure of the arts institutions. All professionals consider that arts education promotes inclusive spaces as it allows for the participation and free expression of its participants. Likewise, they consider that accessibility is not really implemented and that the implementation of activities in arts institutions should favor the participation of users. In conclusion, there is a need to train professionals in inclusive arts education, to encourage collaboration between professionals and to implement inclusive strategies to promote participation and social inclusion.